Early Christian spirituality according to the First Epistle of John: The identification of different 'lived experiences' - van der Merwe, Dirk G. (HTS Teologiese Studies / Theological Studies, 2013)
The interest in this article is early Christian spirituality. The word 'spirituality' is used here denoting 'a lived experience'. Therefore, the article focuses on religious experience in an early Christian community as explicated in the first chapter of the First Epistle of John. Three different lived experiences are denoted here, culminating in the last one: 'having fellowship with the divine'. The first two experiences (experience through physical senses, experience through spiritual senses) pave the way to establish fellowship with the divine. For the author of 1 John, the purpose (ἵνα) of these lived experiences is to have (ἵνα) complete joy, another form of experience. These three lived experiences express three different configurations of spirituality.
free
Keywords: BIBLE. Epistles of John; BIBLE. New Testament; CHRISTIAN communities; CHRISTIAN spirituality; EXPERIENCE (Religion)